p53 and NFκB regulate microRNA-34c expression in porcine ovarian granulosa cells - Yuan XU; Ai-ling ZHANG; Guang XIAO; Zhe ZHANG; Zan-mou CHEN; Hao ZHANG; Jia-qi LI (Journal of Integrative Agriculture, 2016)
MicroRNAs (miRNAs) are endogenous 18–24 nucleotide (nt) non-coding RNAs, some of which have been indicated to play key roles in granulosa cells (GCs) function. However, little is known about how the miRNA gene expression itself is regulated in the GCs. Our previous study showed that miR-34c, identified to be a pro-apoptotic and anti-proliferative factor in many cell types, exerted the same effects in porcine GCs. Here, the transcriptional regulation of miR-34c expression in GCs was further investigated. 5′ rapid amplification of cDNA ends (RACE) assay indicated that the pri-miR-34c transcription start site was located in 1 556 bp upstream of pre-miR-34c. With dual-luciferase reporter assay, we confirmed a 69 bp core promoter region (–1 799 bp/–1 730 bp) was indispensable for the transcription of miR-34c. Chromatin immunoprecipitation (ChIP) assay demonstrated that p53, p50, and p65 could bind to the transcription factor binding sites within the 69 bp core promoter region. In addition, deletion of transcripition factor binding sites resulted in obvious change of the miR-34c promoter activity. Finally, using overexpression and knockdown of p53, p50, and p65 strategies, we showed that p53 and p50 could positively regulated miR-34c expression, whereas p65 neletively regulated miR-34c expression in GCs. Our results provide new data about the transcription regulatory mechanism of miRNA genes in GCs.